Synthesis and characterization of new dextran-acrylamide gels - ABDURRAHMANOĞLU, SUZAN (WILEY, 2007)
Dextran-acrylamide gels were synthesized in a single step reaction by using 4,4'-azobis(4-cynovaleric acid) as bi-functional initiator at 60 degrees C. Corresponding acrylamide (AaM) gels in the absence of dextran were also prepared for comparison. Several parameters such as reaction period (6, 12, and 24 h), monomer and crosslinker concentrations were varied and their effects on the properties of gels were investigated. Gels were characterized by their mechanical and swelling behaviors and in terms of structural changes using SEM. It was observed that swelling degree decreased by increasing the monomer concentration due to formation of more crosslinking points that cause tighter network structure. Mechanical measurements showed that elastic modulus of AaM gels was higher than that of dextran-AaM gel which indicating the importance of dextran concentration on the flexibility of the network.
Keywords: biodegradable; gels; networks; polysaccharides; GRAFT-POLYMERIZATION; IMMOBILIZATION; MICROSPHERES